Disruption of chlorophyll metabolism and photosynthetic efficiency in winter jujube (Ziziphus jujuba) Induced by Apolygus lucorum infestation - Tan, Wei; Yin, Qi; Zhao, Haipeng; Wang, Mengyao; Sun, Xia; Cao, Hui; Wang, Deya; Li, Qingliang (Frontiers in Plant Science, 2025)
Apolygus lucorum, a cosmopolitan Hemiptera insect, poses a significant threat to Ziziphus jujuba (jujube), causing symptoms such as mottled chlorosis. However, the mechanisms through which A. lucorum affects chlorophyll biosynthesis and degradation remain unclear. This study investigates the effects of A. lucorum infestation on chlorophyll metabolism and photosynthetic performance in winter jujube leaves. Results revealed a substantial reduction in chlorophyll a and b content, which was strongly correlated with decreases in key photosynthetic parameters, such as the Photochemical Performance Index (PIABS) and electron transport efficiency (ψ(Eo)). Infestation downregulated genes critical for chlorophyll biosynthesis, such as HEMA, HEMB, and chlG, leading to a bottleneck in chlorophyll production. Concurrently, chlorophyll degradation pathways were upregulated, with genes like PAO and RCCR driving increased chlorophyll catabolism. This imbalance between reduced synthesis and accelerated degradation exacerbated chlorophyll loss, impairing photosynthetic capacity. Furthermore, the application of exogenous H2O2 intensified chlorophyll degradation, particularly in A. lucorum-infested leaves. The accelerated degradation of chlorophyll, coupled with reduced light-harvesting efficiency, contributed to oxidative stress and further impaired the photosynthetic machinery, despite an increase in antioxidant enzyme activity. These findings underline the critical role of chlorophyll metabolism in maintaining photosynthetic efficiency in winter jujube under A. lucorum infestation. It underscores the need for targeted strategies to protect chlorophyll synthesis and limit its degradation in order to mitigate the detrimental effects of A. lucorum-induced stress.